N-(4-(6-(4-nitrophenyl)-4-phenyl-1,3-diazabicyclo[3.1.0]hex-3-ene-2-yl)phenyl)acetamide - Mahdi Ardyanian; Hamzeh Kiyani (Molbank, 2012)
As a result of three-component one-pot reaction of trans-2-benzoyl-3-(4-nitrophenyl)aziridine with 4-acetamidobenzaldehyde and ammonium acetate, N-(4-(6-(4-nitrophenyl)-4-phenyl-1,3-diazabicyclo[3.1.0]hex-3-ene-2-yl)phenyl)acetamide was obtained in good yield. The newly synthesized compound exhibit interesting photochromic behavior in the solid and solution state. The structure of the synthesized compound was confirmed by elemental analysis, 1H-NMR, 13C-NMR and UV-Visible spectral data.